Enhancing Passing and Dribbling Skills: The Impact of Integrating Small-Sided Games and Speed Endurance Training - Fahrezi, Alfero; Bulqini, Arif (Universitas Negeri Surabaya, 2025)
Purpose: This study aims to investigate the impact of combining Small-Sided Game (SSG) and Speed Endurance Training (SET) on the passing and dribbling abilities of football players in the student activity unit (UKM) at Universitas Negeri Surabaya. Materials and Methods: This study employed a quantitative approach with a Pre-Experiment method and One-Group Pretest-Posttest design, using non-random sampling and no control group. Eighteen soccer UKM members at Surabaya State University participated, completing pre-tests to assess passing and dribbling abilities before a four-week training program combining SSG and SET, conducted three times a week. Post-tests evaluated skill improvements and analyzed the results to determine the training's effectiveness. Result: The findings showed a significant improvement in passing ability with the right foot (60.38%) and dribbling (1.4%), while the left-foot passing ability decreased by 5.56%. Additionally, a paired sample t-test analysis revealed significant differences in right-foot passing and dribbling skills, demonstrating the effectiveness of the training program. Conclusion: SSG and SET training effectively enhances passing and dribbling skills, with a more pronounced improvement in right-foot passing. These results suggest the need for further emphasis on left-foot passing in training programs and potentially increasing the frequency or duration of sessions for optimal outcomes.